HDAC inhibitors block innate immunity - Bode, Konrad A.; Dalpke, Alexander (Blood, 2011)
In this issue of Blood, Roger and colleagues present data on the magnitude of influence that broad-spectrum HDAC inhibitors exert on TLR-driven immune responses, thus demonstrating that HDAC inhibitors are immunosuppressive drugs.Histone deacetylase (HDAC) inhibitors have become promising candidates for the treatment of different types of cancer. “At least 80 clinical trials are under way, testing more than eleven different HDAC inhibitory agents,”1p1 for their antitumor effect in hematologic and solid malignancies. The HDAC inhibitor vorinostat is now an approved add-on therapy for cutaneous T-cell lymphoma.2 HDAC inhibitors induce growth arrest, differentiation, and programmed cell death, and inhibit invasion and angiogenesis. However, over the years, evidence has accumulated showing that HDAC inhibitors also have immunomodulatory activity even in nonapoptotic concentrations. Although HDAC inhibitors increase acetylation of histones, a condition associated with increased transcriptional accessibility, multiple reports have shown that HDAC inhibitors possess suppressive effects on immune response gene induction. Individual cytokines that are induced by microbial components triggering Toll-like receptors (TLRs) were reported to be inhibited by HDAC inhibitors.3-5 Yet, the extent of those inhibitory effects and possible functional consequences during infections were largely unknown.
Gesehen am 31.03.2022
Comment on Roger et al, page 1205